Achieving consensus : tools and techniques - Scott, Jon (Crisp Pub. Menlo ParkUS, 1996)
Itemises and discusses individual skills and experiences which may help or hinder the process of concensus. Looks at factors which promote successful meetings, including: ensuring appropriate respresentation; and, creating a code of conduct which ensures the inclusion of everyone's view. Provides tools and techniques for coping with behavioural obstacles such as: dominating behaviour, and lack of participation. Also provides tools and techniques for removing decision obstacles, and thus enabling concensus. Some of the decision obstacles identified are: splinter groups, endless discussion, and losing focus.